ENVIRONMENTAL AND SOCIAL MANAGEMENT PLAN (ESMP) for Pilot of Climate Smart Agricultural InnovaGons and Climate InformaGon Service Technologies in Senegal - Kwaw, Adams; Sene, Serigne Oumar; Koita, Mamoutou (Accelerating Impacts of CGIAR Climate Research for Africa, 2024)
The Environmental and Social Management Plan (ESMP) of the AICCRA Senegal project has been developed to address the environmental and social risks associated with the implementation of climate-smart agricultural innovations (CSA) and climate information service technologies (CIS). Funded by the World Bank's International Development Association, the project, led by the International Biodiversity Alliance and CIAT, targets six priority African countries, including Senegal. The AICCRA Senegal project plans to establish 62 demonstration farms in 51 farming communities. In order to prevent any potential negative impact, a specific examination of the sites has confirmed the presence of environmental and social risks, necessitating the implementation of this ESMP. The ESMP will serve as a guide for managing and mitigating these risks, and will be consulted regularly with stakeholders, as well as being updated as the project evolves.